84: IS HOSPITALIZATION RATE ASSOCIATED WITH SEXUALITY? A TIME-PERIOD STUDY IN THE LARGEST REFERRAL HOSPITAL IN NORTHWEST OF IRAN. (8th February 2017) - Talebpour, Amin; Ghogazadeh, Morteza; Ghodrati, Parisa; Rezaie, Zohreh
Abstract : Background and aims: The hospitalization rate differences between male and female patients could facilitate management of hospital wards and enhance their efficiency. The aim of this study was to determine the association between sexuality and hospitalization rate by annual hospitalization statistics of one of the Tabriz University of Medical Sciences hospitals according to hospitalization wards. Methods: A Cross-sectional study was conducted. All 30260 records of hospitalized patients of Imam Reza referral Hospital in 1393 included in the study. Data was extracted based on a checklist designed by authors. In order to determine the relations between the variables, Chi-Square test was applied and the P-value was considered less than 0.05. The obtained data were analyzed by software SPSS.16. Results: Of 30260 Cases, 52.26% were male and 47.73% were female. There was no significant difference among male and female hospitalized patients. The highest hospitalization rate for men was in the orthopedics ward with 20.04% (3302 of 16158 male patients) while it was 14.2% (3054 of 13877 female patients) for women in surgery ward. The least significant statistical difference between male and female hospitalization rates was observed in renal ward with 49.85% (683 patients) male and 50.15% (687 patients) female of total patients hospitalized in this ward. The significant statistical difference between male and female hospitalization rates was observed in orthopedic with 71.31% (3302 patients) male and 28.69% (1328 patients) female patients. Vice versa, in the thorax ward, 71.1% (1200 patients) were female and 28.9% (486 patients) were male patients. Conclusion: There was no any significant difference between male and female hospitalized patients expect 5 clinical wards including gastroenterology, thoracic surgery, orthopedics, trauma and urology. It seems that gender is in a direct association with these 5 disease type. This matter should be considered by policy makers and stakeholders.